Archaeology of Pacific Oceania - Carson, Mike T., author.
1 online resource.
Keywords: "Now in its second edition, this book integrates a region-wide chronological narrative of the archaeology of Pacific Oceania. How and why did this vast sea of islands, covering nearly one-third of the world's surface, come to be inhabited over the last several millennia, transcending significant change in ecology, demography, and society? What can any or all of the thousands of islands offer as ideal model systems toward comprehending globally significant issues of human-environment relations and coping with changing circumstances of natural and cultural history? The new second edition delivers the most updated and comprehensive information for addressing the core fundamental questions about Pacific Oceanic archaeology, based largely on the author's investigations throughout the diverse region"--